CEPC and Gwadar Port: Viabilities and Challenges - Lin, Wang; Iftikhar, Rukhsana (Annals of Human and Social Sciences, 2024)
The objective of this study is review of Gwadar port , its importance in geostatic and geo economic dynamics and its undeniable challenges for Pakistan. There are many geo-political theories prevailing about the functional operation of this port due to the interest of various players Gwadar was inaugurated by Pervaiz Musharaff in 2007 after releasing from Omani Control. There are big plans for this southern coastal city of Balochis tan and China is investing 700 million US dollars to transform this city from a shady town to the hub of international trade for central Asia, China, Afghanistan and western countries. But the peaceful development is very slow, and the idea of business is much slower. It is very difficult to attract private investors . The oil and energy will be directly import from Middle though Pakistan ,s oil pipeline, which ultimately linked with China. This port could increase the size of Pakistan’s maritime trade. There are many geo-political theories prevailing about the functional operation of this port due to the interest of various players. Secondary data has consulted to analyze the local and international factor in the smooth function of Gwadar port to international trade. Qualitative research method has followed by using Pakistan Statistical Yearbook, Pakistan economic survey reports , newspapers, District development Statistics of Baluchistan a to suggest for the eliminating of internal factors to strengthen the idea of using this port as international hub of trade. The idea of economic development can be achieved if Pakistan would be able to provide a peaceful environment for Chinese and other countries. Gwadar port will ease Pakistan’s economy and it is recommended to make this area peaceful for investors.